2022
DOI: 10.1111/clr.14014
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficiency and cytocompatibility of different decontamination methods on titanium and zirconium surfaces

Abstract: Objectives:The purpose of this study was to investigate the efficiency of different implant-decontamination methods regarding biofilm modification and potential cytotoxic effects. Therefore, the amount of biofilm reduction, cytocompatibility, and elementary surface alterations were evaluated after decontamination of titanium and zirconium surfaces.Material and Methods: Titanium and zirconium disks were contaminated with a newly developed high-adherence biofilm consisting of six microbial species.Decontaminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
(89 reference statements)
1
8
0
Order By: Relevance
“…The high cleaning efficacy of the two mechanical decontamination methods (rotating TiB and AP) observed in the present study is in agreement with results from previous in vitro studies (e.g., Al‐Hashedi et al, 2017; Dostie et al, 2017; Hui et al, 2021; Ichioka et al, 2022; Matthes et al, 2017; Stein et al, 2022). Toma et al (2018) showed that the reduction of a single‐bacterial biofilm by use of a TiB was similar to that achieved by AP.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The high cleaning efficacy of the two mechanical decontamination methods (rotating TiB and AP) observed in the present study is in agreement with results from previous in vitro studies (e.g., Al‐Hashedi et al, 2017; Dostie et al, 2017; Hui et al, 2021; Ichioka et al, 2022; Matthes et al, 2017; Stein et al, 2022). Toma et al (2018) showed that the reduction of a single‐bacterial biofilm by use of a TiB was similar to that achieved by AP.…”
Section: Discussionsupporting
confidence: 93%
“…The use of chemical agents (AEW and NAC) as adjuncts to the mechanical cleaning protocols provided no relevant overall benefit over saline. No treatment modality, however, resulted in complete biofilm removal.The high cleaning efficacy of the two mechanical decontamination methods (rotating TiB and AP) observed in the present study is in agreement with results from previous in vitro studies(e.g., Al-Hashedi et al, 2017;Dostie et al, 2017;Hui et al, 2021;Ichioka et al, 2022;Matthes et al, 2017;Stein et al, 2022) Toma et al (2018). showed that the reduction of a single-bacterial biofilm by use of a TiB was similar to that achieved by AP.…”
mentioning
confidence: 95%
“…Tan et al found minimal surface alterations with the use of air‐powder abrasive devices and plastic curettes on zirconium surfaces and no difference in biofilm adhesion on biofilm‐contaminated titanium and zirconium discs for the following decontamination methods: titanium curette, plastic curette, air‐powder abrasion and ultrasonic scaler with a stainless steel tip 41 . On the other hand, Stein et al recently found a significant reduction in bacterial presence on zirconium surfaces compared with titanium surfaces after using an ultrasonic scaler with a stainless steel tip, glycine or erythritol air‐powder abrasion 42 . However, both studies did not investigate the effect of the presence or absence of a suprastructure on cleaning efficacy.…”
Section: Discussionmentioning
confidence: 98%
“…41 On the other hand, Stein et al recently found a significant reduction in bacterial presence on zirconium surfaces compared with titanium surfaces after using an ultrasonic scaler with a stainless steel tip, glycine or erythritol air-powder abrasion. 42 However, both studies did not investigate the effect of the presence or absence of a suprastructure on cleaning efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This finding can be associated with the direct preservation of the valleys region microstructure (Balderrama et al., 2020), which are the preferred cell adhesion sites on the surfaces, avoiding the peaks. This first phase determines the further behavior of the cells in contact with the implant surface (i.e., cell proliferation and differentiation), which could facilitate successful re‐osseointegration (Cao et al., 2018; Stein et al., 2023).…”
Section: Discussionmentioning
confidence: 99%